2021
DOI: 10.21037/tcr-20-2794
|View full text |Cite
|
Sign up to set email alerts
|

A novel nomogram for predicting survival of patients with poorly differentiated gastric adenocarcinoma

Abstract: Background: Poorly differentiated gastric adenocarcinoma (PDGA) is a common adenocarcinoma with less glandular structure in gastric cancer. To date, the factors affecting its prognosis remain unclear. In this study, we establish a novel prognostic nomogram for PDGA. Methods:We screened the Surveillance, Epidemiology, and End Results (SEER) database and downloaded data from PDGA patients who underwent surgery between 2010 and 2015. We explored their clinicopathological characteristics and important prognostic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The accurate prediction of nomograms has been proved to be significant for clinical decisionmaking in previous studies. 10,[19][20][21] In this multicenter study, the prognostic factors included in the nomograms, which proved to have good predictive ability. Ever since Vichow 22 proposed the "tumor-inflammation" theory in 1863, many studies have confirmed that inflammatory indicators such as NLR and PLR are related to tumor occurrence, development and prognosis.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The accurate prediction of nomograms has been proved to be significant for clinical decisionmaking in previous studies. 10,[19][20][21] In this multicenter study, the prognostic factors included in the nomograms, which proved to have good predictive ability. Ever since Vichow 22 proposed the "tumor-inflammation" theory in 1863, many studies have confirmed that inflammatory indicators such as NLR and PLR are related to tumor occurrence, development and prognosis.…”
Section: Discussionmentioning
confidence: 79%
“…25 Studies have shown that the increase of PLR in gastric cancer patients before treatment is significantly correlated with pathological types and affects the prognosis of gastric cancer. 9,20 Serum levels of various tumor markers may be elevated in patients with gastric cancer. It has been reported that the serum levels of various tumor markers (such as CEA and CA199, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The Cox and Frailty models of survival analysis were used and then compared with C-index 13 . Other researchers have presented nomograms, which are the graphical representation to intuitive perception of clinicians in Colorectal cancer (CRC) and GC patients 11 , 19 , 20 . A nomogram, a simple graphical visualization combining and quantifying all independent prognostic factors, plays an increasingly vital role in medical sciences and clinical studies 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The Cox and Frailty models of survival analysis were used and then compared with C-index 13 . Other researchers have presented nomograms, which are the graphical representation to intuitive perception of clinicians in Colorectal cancer (CRC) and GC patients 11,19,20 . A nomogram, a simple graphical visualization combining and quantifying all independent prognostic factors, plays an increasingly vital role in medical sciences and clinical studies 21 .…”
Section: Introductionmentioning
confidence: 99%